Soy Germ Protein With or Without-Zn Improve Plasma Lipid Profile in Metabolic Syndrome Women - HERY WINARSI; SIWI PRAMATAMA MARS WIJAYANTI; AGUS PURWANTO (HAYATI Journal of Biosciences, 2012)
The aim of this research was to determine the effect of soy germ protein on lipid profile of metabolic syndrome (MetS) patients. Respondents were 30 women with criteria, i.e. blood glucose level > normal, body mass index > 25 kg/m2, hypertriglyceridemia, low cholesterol-HDL level, 40-65 years old, living in Purwokerto, and signed the informed consent. The project was approved by the ethics committee of the Medical Faculty from Gadjah Mada University-Yogyakarta. Respondents were divided into three randomly chosen groups consisting of ten women each. The first, second, and third groups were treated, respectively, with milk enriched soy germ protein plus Zn, milk enriched soy germ protein (without Zn), and placebo for two months. Blood samples were taken at baseline, one and two months after observation. Two months after observation the groups consuming milk enriched with soy germ protein, both with or without Zn, had their level of cholesterol-total decrease from 215.8 to 180.2 mg/dl (P = 0.03), triglyceride from 240.2 to 162.5 mg/dl (P = 0.02), and LDL from 154.01 to 93.85 mg/dl (P = 0.03). In contrast, HDL increased from 38.91 to 49.49 mg/dl (P = 0.0008). In conclusion, soy germ protein can improve lipid profile, thus it can inhibit atherosclerosis incident.